Tuning Cobalt‐Free Nickel‐Rich Layered LiNi0.9Mn0.1O2 Cathode Material for Lithium‐Ion Batteries. Issue 12 (17th June 2020) - Ma, Rui; Zhao, Zhikun; Fu, Jiale; Lv, Haijian; Li, Chunli; Wu, Borong; Mu, Daobin; Wu, Feng
Abstract: As the demand for high‐energy‐density batteries becomes more and more urgent, cathode materials of high‐energy lithium‐ion batteries have received widespread attention. LiNi x Co y Mn1‐ x ‐ y O2 (NCM) ternary materials with high nickel and low cobalt content as well as a high cut‐off voltage are continually pursued. Here, a nickel‐rich cobalt‐free cathode material, LiNi0.9 Mn0.1 O2, was synthesized by using a co‐precipitation method to achieve a stable structure and excellent electrochemical performance. It shows a discharge specific capacity of 190 mAhg −1 in the first cycle at a rate of 0.2 C, and a capacity retention of 93 % over 150 cycles at 2.7–4.3 V. It also exhibits excellent electrochemical performance under high cut‐off voltage. The initial discharge specific capacity reaches 197.5 mAhg −1 at 0.2 C within 2.7 to 4.5 V, and the capacity retains 188.9 mAhg −1 after 100 cycles. The work provides an alternative cathode material for high‐energy‐density and cost‐effective lithium‐ion batteries. Abstract : Future possibilities : The cobalt‐free nickel‐rich layered cathode material LiNi0.9 Mn0.1 O2 with a stable structure and excellent electrochemical performance is synthesized by using a co‐precipitation method. LiNi0.9 Mn0.1 O2 exhibits a capacity retention of 93 % after 150 cycles at 0.2 C at 2.7–4.3 V and a high thermal decomposition temperature of 234°C. Considering the material contains no cobalt, attaining the present comprehensive performance is attractive.